Control of bacterial pathogens associated with mastitis in dairy cows with natural antimicrobial peptides produced by lactic acid bacteria - Pieterse, Renee (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Microbiology))--Stellenbosch University, 2008.